Permanent School Closures and Crime: Evidence from Scotland - Daniel Borbely; Markus Gehrsitz; Stuart McIntyre; Gennaro Rossi (Institute of Labor Economics (IZA), 2023)
In this article we study the effects of permanent school closures on crime. We leverage the closure of over 300 schools in Scotland between the school years 2006/07 and 2018/19, and employ a staggered difference-in-differences design on a matched sample. We find that neighbourhoods affected by school closures experience a reduction in crime of about 9% of a standard deviation, relative to areas where schools remained open. This effect is mainly driven by a reduction in violent and property crimes. We provide evidence on several mechanisms explaining the negative crime effect, such as changes in neighbourhood composition and reductions in school-level segregation.
Keywords: I38; R20; K42; 330; crime; school closures; neighbourhoods